Menuju Komunitas Kolaboratif: Implikasi Teori Intersubjektivitas dalam Dilema Komunitas Religius Multikultur - Apriano, Alvian (Fakultas Teologi, Universitas Sanata Dharma, 2024)
This article presents how philosophical thinking practically gives relational strength to multicultural religious communities. Maurice Merleau-Ponty talks about intersubjectivity, the benefits of which are so binding in inter-body relations. Steven McCormack talks about the importance of interpersonal communication as a strength of relationships within the community. David W. McMillan and David M. Chavis talk about the importance of